EFFEKTIVITAS PENYULUHAN ASI EKSLUSIF TERHADAP PENGETAHUAN DAN SIKAP IBU BAYI DI PUSKESMAS GANDUS - Muhammad Yusuf, Yulianto, Eddy Susanto, Hana Yuniarti, Mardiana (Jurusan Gizi, Poltekkes Kemenkes Palembang, 2021)
Background : The lowest exclusive breastfeeding coverage in Palembang is at the Gandus Health Center in Palembang at 41.79%, far from the national target of 80%. To increase coverage, one of them is exclusive breastfeeding counseling on the knowledge and attitudes of mothers and babies at the Gandus Health Center which is expected to increase the coverage of exclusive breastfeeding at the Gandus Health Center. The Purpose : The purpose of this research is to analyze the effectiveness of counseling on the knowledge and attitudes of the mother and baby. Methods : The research method uses an experimental design with a One Group Pre Test - Post Test design, the number of samples tested is 77 mothers of infants aged (0-60) months. Results : The results of the study showed that there was an effect of exclusive breastfeeding counseling on increasing the knowledge and attitudes of the baby's mother. Conclusion : The effectiveness of counseling can significantly increase the knowledge and attitudes of respondents. Suggestions : It is suggested to the Puskesmas, that they should always provide counseling on exclusive breastfeeding to mothers of babies more effectively.